Comparison of Arabic and Cyrillic texts of Arkalık Batır and Bazar Batır Jırs - BAYAN; Ali (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2025)
Kazakh historical jırs are one of the important literary works of Kazakh history and literature. Most of the historical jırs were written in Arabic letters and later and later transcribed into the Cyrillic-based Kazakh alphabet. Of these jırs, Bazar Batır and Arkalık Batır are important texts that describe the political, historical and social conditions of the Kazakh society in the 19th century. The jır of Bazar Batır is one of the jırs that has been studied very little so far. This jır was transcribed from its original Arabic-script version into Cyrillic script. Various alphabet and language problems arose in this transfer. The reason for these problems was that there was no basic alphabet used in the 19th century and the letters in the alphabet changed several times, and different letters were used by each writer and each publishing house. Because the Arabic alphabet used for the Kazakh language could not represent to some sounds in this language, several sounds were shown with the same letter. In addition, for various reasons, problems such as some word changes, divergent readings of certain sounds, and leaving lines untranslated were observed in the transfer of the Arabic-script text into the Cyrillic script. In this article, the Arabic and Cyrillic texts of the Bazar Batır and Arkalık Batır jırs were compared, their features and differences were determined, and the problems encountered in text transfer were examined. During the examination, not only the differences in the transfer from Arabic to Cyrillic letters, but also the writing features of the copies written in the two alphabets were discussed. The Arabic-lettered text of the Bazar Batır jır, registered at number 358 in the Sirek Kitaptar Korı of the Almatı Ortalık Gılım Library, and the Cyrillic-lettered copies published in the 60th volume of Babalar Sözü, consisting of one hundred volumes, as well as the Arabic-lettered text of the Arkalık Batır jır, registered at number 546 in the Koljazbalar Section of the Almatı Ortalık Gılım Library, and the Cyrillic-lettered copies published in the 61st volume of Babalar Sözü, consisting of one hundred volumes, were compared.